Escola e museu: a relação entre educação e patrimônio cultural, em Vila Cruz/RS, geoparque Quarta Colônia - Scapin, Eloi Piovesan (2022)
In the course of its history, the humanity has built several heritage, both material and immaterial. Postponed to the next generations as an inheritance, these heritage constitute memory and identity of the social groups to which they belong. The village termed Vila Cruz, located in the cyty of Nova Palma/RS, is one of those places where copious cultural heritage, from the process of Italian colonization in the region known as Quarta-Colônia, is still protected. These cultural heritage include buildings, objects and instruments of daily use, religiosity, habits and customs, from which the stone houses, Capitals, Santa Cruz Chapel, big houses and Cultural Filo stand out. State Elementary School Pe. João Zanella and the Vila Cruz Museum have provided pedagogical activities aimed at these numerous legacies, where heritage education is configured as a consistent methodological orientation, precisely because heritage assets are the objective of their studies and actions. In this sense, the aim this study is to demonstrate how the School and the Museum, based on the relationship between education and cultural heritage, objetive the knowledge, preservation and appreciation of the history and legacies found in this village. In establishing this path, it is based on relevant bibliographic references and other considerable documentary sources, such as old records and period photographs, as well as on visits and observations of different patrimonies in loco. As a result of this effort, the booklet Heritage Education: Knowing, Preserving and Valuing the Cultural Heritage of Vila Cruz – Nova Palma/RS presents itself as the pedagogical support that provides various possibilities for teaching and learning, since it permeates, in a playful and dynamic, for the diverse cultural patrimonies of Vila Cruz. Therefore, the importance of education for the creation and consequent maintenance of bonds between students and their references is reiterated, thus making the work of educational institutions and museums essential, which together reinforce the awareness of subjects regarding the firming of its memory and its identity. At the same time, the Quarta Colônia Geopark – Aspirant Unesco reinforces even more intent, since, among its initiatives, it seeks a consistent regional development allied to the enhancement of the sense of belonging of its fellow citizens regarding their origins and place. Finally, it is tracing this path that will allow the formation of subjects that are increasingly critical, creative and sensitive about their own history, as well as conscious about the importance of their cultural heritage.